2021
DOI: 10.1002/emp2.12362
|View full text |Cite
|
Sign up to set email alerts
|

The impact of adoption of an electronic health record on emergency physician work: A time motion study

Abstract: Objective: We assessed the impact of the transition from a primarily paper-based electronic health record (EHR) to a comprehensive EHR on emergency physician work tasks and efficiency in an academic emergency department (ED). Methods: We conducted a time motion study of emergency physicians on shift in our ED. Fifteen emergency physicians were directly observed for two 4-hour sessions prior to EHR implementation, during go live, and then during post-implementation. Observers performed continuous observation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
(14 reference statements)
1
13
0
Order By: Relevance
“…To the best of our knowledge, this is the first survey study to investigate the level of physician workload tethered to non-physician-patient communication work tasks characterized by paperwork during outpatient encounters and further explore its latent subgroups among Chinese physicians and identify the differences between the subgroups across demographic characteristics. Existing studies often simply adopted several objective workload indicators (e.g., work time, and the number of patient seen) for physician workload assessments in China ( 11 ), and currently, in China Health Statistics Yearbook, physicians' workloads were generally counted and measured using the average daily number of outpatients and average number of hospital beds per day that an physician undertakes ( 7 ); and none of them have examined the physician workload tethered to paperwork during outpatient encounters, whereas internationally current studies regarding the clerical burden of physicians have focused on the effect of adoption of electronic health records on physician workload ( 43 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first survey study to investigate the level of physician workload tethered to non-physician-patient communication work tasks characterized by paperwork during outpatient encounters and further explore its latent subgroups among Chinese physicians and identify the differences between the subgroups across demographic characteristics. Existing studies often simply adopted several objective workload indicators (e.g., work time, and the number of patient seen) for physician workload assessments in China ( 11 ), and currently, in China Health Statistics Yearbook, physicians' workloads were generally counted and measured using the average daily number of outpatients and average number of hospital beds per day that an physician undertakes ( 7 ); and none of them have examined the physician workload tethered to paperwork during outpatient encounters, whereas internationally current studies regarding the clerical burden of physicians have focused on the effect of adoption of electronic health records on physician workload ( 43 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, assessment and management of physician workload tethered to the related paperwork during outpatient encounters is of great importance to promote physical and mental well-being for physicians and decrease the risk for burnout, as well as to increase the time available for direct interaction with patients and further improve the quality of physician-patient interaction, thereby improving physician and patient satisfaction. Although current studies regarding the clerical burden of physicians have assessed the impact of adoption of electronic health records on physician workload ( 43 46 ), no previous studies have investigated the level of workload among physicians tethered to the related paperwork during outpatient encounters and its characteristics, and have assessed whether there exist distinctive workload clusters or patterns in these physicians, especially in China. Therefore, this study focused on the physician workload while performing the related paperwork during outpatient encounters.…”
Section: Introductionmentioning
confidence: 99%
“…EHR/EMR implementation and adoption poses unique challenges as an ED cannot shut down while testing a system and the impact of ED physician allocation and efficiencies are different than office-based practices [ 50 ]. A recent Ontario study found a reduction in ED physician efficiencies over time that did not recover to baseline after the implementation of an ED EHR [ 51 ]. However an important objective of the digital health strategy is to improved communications with providers across healthcare sectors.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that treatment by foreign nurses is negatively associated with satisfaction regarding communication and overall perception of care [65]. Interventions to improve consumers information regarding their wait time in the ED are needed as patients have reported having access to wait time information positively impacts on their overall satisfaction with care in the ED [12].…”
Section: Consumers Satisfactionmentioning
confidence: 99%
“…Further, system usability varies by brand and setting [9][10] Previous research has explored the association of EHRs on workflow and quality of care. Some studies report improvements after EHR implementation [11] while others suggest that EHR implementation may impact clinicians' task allocation and reduce efficiency during and after implementation [12][13][14] indicating needs for improvements in usability, functionality and workflow optimisation [13]. Research on barriers to and strategies for successful implementation of digital information systems exists [see e.g.…”
Section: Introductionmentioning
confidence: 99%